2013
DOI: 10.1111/gwmr.12014
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Environmental Performance of In Situ Thermal Remediation Technologies Using Life Cycle Assessment

Abstract: In situ thermal remediation technologies provide efficient and reliable cleanup of contaminated soil and groundwater, but at a high cost of environmental impacts and resource depletion due to the large amounts of energy and materials consumed. This study provides a detailed investigation of four in situ thermal remediation technologies (steam enhanced extraction, thermal conduction heating, electrical resistance heating, and radio frequency heating) in order to (1) compare the life‐cycle environmental impacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Other studies have also reported a significant contribution to the impact in this category due to the use of fossil fuels [17,39,40]. In this study the environmental remediation implied a total path traveled by a truck of 6194 km, while the van traveled 2744 km.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Other studies have also reported a significant contribution to the impact in this category due to the use of fossil fuels [17,39,40]. In this study the environmental remediation implied a total path traveled by a truck of 6194 km, while the van traveled 2744 km.…”
mentioning
confidence: 67%
“…In this sense, life cycle assessment (LCA) is an option to evaluate the environmental behavior of products or process. In fact, LCA was previously used for the evaluation of remediation technologies in various scenarios, such as soil pollution by heavy metals, polychlorinated biphenyls and volatile organic compounds (VOC) [14,[16][17][18][19][20][21]. During LCA evaluation, the identification of primary and secondary impacts in remediation technologies is important; primary impacts are those related to residual contamination left in the subsurface during and after remediation, while secondary impacts refer to the consumption of resources and generation of emissions in other stages of the remediation life cycle of the project [14].…”
Section: Introductionmentioning
confidence: 99%
“…If the excavation alternative is selected for this site, then results indicate that it is important to investigate whether the environmental impacts of this method can be reduced by methods such as local soil treatment and recycling of treated soil. A study on optimizing the environmental performance of in-situ thermal remediation technologies (Lemming et al 2013) has shown that LCA can be used to identify and test possible environmental improvements to the remediation technology.…”
Section: Discussionmentioning
confidence: 99%
“…The energy usage to reach such temperatures typically range from 150 to 600 kWh per cubic meter of material treated, depending on site-specific parameters such as treatment zone size, water content, groundwater flow, COC boiling points, target treatment temperature, and remedial goals. The required energy is typically generated from electricity or fossil fuel, with a substantial carbon footprint (Lemming et al 2013). A clear objective of many thermal projects is to minimize this energy usage.…”
Section: Introductionmentioning
confidence: 99%